Contribution to the taxonomic revision of the order Oscillatoriales - Hauerová, Radka (Jihočeská univerzita, 2021)
With the increased use of molecular data, especially the 16S rRNA gene and the following 16S-23S ITS region, many new species and genera have been described in recent years. At the same time, numerous traditional taxa have been recognized as polyphyletic and subsequently subjected to the revisionary process leading to their smaller size and narrower definition. However, there are many species and genera for which no molecular data are available as they were described long before the invent of the sequencing techniques. Thus, it is difficult to allocate their position in the modern phylogenies and move forward with their revisions. This thesis focuses on several simple filamentous cyanobacteria currently classified in the order Oscillatoriales and on the detail study of their type species. The connection of traditional descriptions with corresponding organism results in possibility to obtain reliable molecular data and study the taxa's relationship with other cyanobacteria. Thus, the reference phylogenetic points were established in this thesis for the traditional genera Arthrospira and Oscillatoria, and subsequently two new genera Limnospira and Tenebriella were introduced together with their reference strains. Clarification of the phylogenetic position of the type species of Oscillatoria, O. princeps, means first step towards resolving the polyphyletic nature of the whole order Oscillatoriales and its taxonomic revision.
Contribution to the taxonomic revision of the order Oscillatoriales